CORRELATION BETWEEN SERUM CALCIUM LEVELS AT ADMISSION AND INFARCT SIZE IN ISCHEMIC STROKE (The Research of Medical Science Review, 2025)
Introduction: Stroke can cause a low quality of life for patients and their families, as well as a great burden and loss for society due to high rates of disability and mortality. Objective: To investigate the correlation between serum calcium levels at admission and infarct size in ischemic stroke patients. Methods: A cross-sectional study was conducted at the Department of Medicine, Sahiwal Teaching Hospital, Sahiwal, involving 100 patients recruited through non-probability consecutive sampling. The sample size was calculated using the WHO calculator with a correlation value of -0.221. Serum calcium levels were measured at admission, and infarct size was assessed using CT scans. Results: The study revealed a significant negative correlation (r = -0.224, p = 0.004) between serum calcium levels and infarct size. Stratified analysis confirmed consistent negative correlations across subgroups, including gender, smoking status, diabetes, and hypertension. Patients with serum calcium levels <8.5 mg/dL had larger infarct sizes compared to those with levels >9.0 mg/dL. Conclusion: It is concluded that lower serum calcium levels at admission are associated with larger infarct sizes in ischemic stroke patients. Serum calcium levels could serve as a prognostic biomarker, aiding in risk stratification and guiding clinical management.